The Influence of Internal Communication and Teamwork on Employee Performance at Natra Bintan A Tribute Portfolio Resort - Akmal Irsan; Arif Adrian (Journal of Multidimensional Management, 2025)
The hospitality industry plays a vital role in tourism by providing accommodation and high-quality service experiences that influence guest satisfaction. This study examines the influence of internal communication and teamwork on employee performance at Natra Bintan, a Tribute Portfolio Resort. Using a quantitative descriptive design with a causal–associative approach, the research involved all 90 employees across various departments, applying a total sampling method. Data were collected via a structured questionnaire tested for validity and reliability, and analyzed with SPSS version 26.0 using descriptive statistics, classical assumption tests, and multiple linear regression. The results show that internal communication (mean = 4.30) and teamwork (mean = 4.38) were rated “very good,” while employee performance achieved an “excellent” rating (mean = 4.53). Regression analysis revealed that teamwork had a strong positive and significant effect (β = 0.868, p < 0.05), whereas internal communication, despite its high score, had no statistically significant effect (β = 0.140, p > 0.05). The model explained 76.6% of the variance in employee performance. These findings highlight teamwork as the primary driver of performance in the hospitality sector, suggesting that management should strengthen collaboration, trust, and psychological safety, while sustaining structured and inclusive communication systems